Internet Bandwidth Management using a MikroTik Router at Shanti Bhuana Institute - Maya Sari; Noviyanti P Noviyanti P; Christian Cahyaningtyas; Mira Mira; Dedy Dedy (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
This study aims to evaluate the effectiveness of bandwidth management using a MikroTik router in optimizing network capacity distribution at Shanti Bhuana Institute. The methods employed include designing a bandwidth allocation scheme based on the priority needs of each unit, implementing the configuration on a MikroTik router, and measuring network performance parameters such as throughput, delay, packet loss, and jitter before and after the implementation of bandwidth management. The testing was conducted in a campus environment involving active users from various academic and administrative units. The results show that the implementation of bandwidth management increased the average throughput from 412 kbps to 1,105 kbps, reduced the average delay from 22.4 ms to 5.2 ms, and decreased jitter from 8.7 ms to 2.1 ms. Packet loss remained below the 1% threshold both before and after implementation. All units received proportional bandwidth allocation according to their operational needs, enabling activities such as web browsing, email communication, and lecture material downloads to run without mutual interference. This study concludes that MikroTik-based bandwidth management is more effective than relying solely on high bandwidth availability, as it is capable of preventing network congestion in multi-user campus environments.